2018
DOI: 10.3390/app8101950
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Phenolic Compounds on Graphene Oxide and Reduced Graphene Oxide: A Batch Experiment Combined Theory Calculation

Abstract: A series of phenolic compounds containing 2-phenylphenol (PPE), bisphenol A (BPA), 4-isopropylphenol (IPE), 4-methylphenol (ME) and phenol (PE) were selected to investigate their major influence factors for their adsorption on graphene oxide (GO) and reduced graphene oxide (RGO) by studying their adsorption isotherms and kinetics. It was found that the adsorption of all tested phenols fitted well with the Freundlich model. In comparison, the adsorption ability of RGO with a stronger π-π interaction was superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 38 publications
(42 reference statements)
1
20
0
Order By: Relevance
“…phenolic compounds) mainly via π-π interaction. 35,36 We focused on the detection of 1-naphthol as a model analyte due to its very high importance and widespread use as enzymatic product in biosensing schemes. [37][38][39][40][41][42] This molecule is also analytically relevant as an industrial phenolic contaminant found in wastewaters and as a biomarker for the assessment of occupational and environmental exposure to carbaryl and naphthalene pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…phenolic compounds) mainly via π-π interaction. 35,36 We focused on the detection of 1-naphthol as a model analyte due to its very high importance and widespread use as enzymatic product in biosensing schemes. [37][38][39][40][41][42] This molecule is also analytically relevant as an industrial phenolic contaminant found in wastewaters and as a biomarker for the assessment of occupational and environmental exposure to carbaryl and naphthalene pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…7b). Also, it is clear that after the GO is reduced, the wrinkled sheets increased and randomly collected [30]. It can be said that oxygencontaining functional groups decrease with increasing reaction temperature and so by removing these groups from the RGO surface, shrinkage occurs [14,29].…”
Section: 𝐷𝑝 = 𝐾𝜆/𝛽𝑐𝑜𝑠𝜃mentioning
confidence: 98%
“…The promising application of the material was demonstrated by its effective reusability (10 successive cycles) without decreased in the removal capacity of the pollutants [137]. The report of Wang et al, (2018) have shown that the adsorption of phenols pollutants; 2-phenylphenol (PPE), bisphenol A (BPA), 4-isopropylphenol (IPE), 4-methylphenol (ME), and phenol (PE) were more effective onto the rGO ( Figure 5) as compared to the GO, attributed to the decreased in electron density in the latter, hence the strong π-π interactions between the phenols and the adsorbent [138]. Tian et al (2019), reported on the rapid adsorption of bisphenol A (3.4 sec), onto hybrid material of graphene oxide with amino functionalized polypropylene (PP-g-DMAEMA/GO).…”
Section: Graphene Graphene Oxides and Reduced Graphene Oxidesmentioning
confidence: 99%
“…In most cases, graphene was shown to have better performance in terms of adsorption capacity as compared to GO and rGO. In comparison to rGO, GO has more oxygen containing functional groups and lesser π electron density [138]. It has been established that the hydrophobic effects of the organic contaminants were the reasons for their strong absorption onto the graphene which occur though π-π interactions [63,140].…”
Section: Graphene Graphene Oxides and Reduced Graphene Oxidesmentioning
confidence: 99%
See 1 more Smart Citation